New Weights in Laplacian Smoothing on Triangular Mesh - Kawa M. A. Manmi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Mesh smoothing is one of the basic procedures for improvement of mesh quality. Most smoothing techniques move vertices of the mesh without changing topology of the connectivity. Laplace smoothing is one of the simplest and efficient algorithm, where in each step vertex of the mesh is move to the barycenter of its neighbors. The only problem with Laplacian smoothing is surface shrinking when it is performed iteratively. In this paper, three relatively simple weights proposed in Laplacian smoothing which has less surface shrinking from the previous weights. The performance and effectiveness of the presented weights are demonstrated on two knowing simply and doubly connected geometrical shapes respectively.